2019
DOI: 10.24846/v28i4y201907
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Factors Affecting the Quality of IoT-based Smart Wearable Devices Using the DANP Method

Abstract: This paper proposes the DANP (DEMATEL-based Analytic Network Process) method so that the factors that affect the quality of IoT (Internet of Things)-based smart wearable devices can be adequately assessed. The proposed method helps to identify and visualize the importance of certain factors (dimensions and criteria), the causal relationship among the factors, the mutual influence upon each other, and their influential weights. A numerical example was presented to illustrate the feasibility and effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Development of the interview guides were informed by a review of relevant literature. 12 13 14 15 16 17 18 The interviews were semi-structured in nature, 19 20 allowing the interviewer (J. J. S.) the flexibility to ask related follow-up questions on topics of interest while also providing the same set of core questions for each type of participant (Veterans and clinicians). All interviews were audio recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of the interview guides were informed by a review of relevant literature. 12 13 14 15 16 17 18 The interviews were semi-structured in nature, 19 20 allowing the interviewer (J. J. S.) the flexibility to ask related follow-up questions on topics of interest while also providing the same set of core questions for each type of participant (Veterans and clinicians). All interviews were audio recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Other cited lifestyle changes were improved diet (5), mindful activity (2), and dedicating more hours for sleep (1). Veterans set specific goals and outcomes related to Fitbit use, including more exercise/movement (12), weight loss (10), improved general health (8), more or better sleep (5), and better cardio health (3). When asked if they would recommend using a Fitbit to other Veterans, all but one indicated that they would recommend it.…”
Section: Benefits From Using the Fitbitmentioning
confidence: 99%
“…("wearable devices" and "ergonomics"); ("iot" and "ergonomics" and "wearable devices" and "multicriteria decision making"); ("iot" and "ergonomics" and "multicriteria decision making"); ("iot" and "multicriteria decision making"); ("wearable devices" and "multicriteria decision making")" generating in titles, abstracts, or keywords. From the literature analysis and expert knowledge 43 criteria were identified in terms of six main attribute groups representing cost-, technology-, HFE-, design-based attributes and attributes related to security and product life cycle management (PLCM) issues; to scrutinize factors affecting Ergonomics 4.0 applications (Rijsdijk & Hultink, 2009;Yang et al, 2016;Jeong et al, 2017;Balog et al, 2019;Büyüközkan & Göçer, 2019;Mashal & Alsaryrah, 2019;Büyüközkan & Güler, 2020;Mashal et al 2020).…”
Section: Applicationmentioning
confidence: 99%
“…Hsu et al [22] adopted DANP to help a parent company select representatives of the local culture for middle and top management positions in their overseas subsidiaries; according to an analysis by an expert panel, positive psychological capital, managerial competencies, integration, and professional competencies should be considered in the selection process. Balog et al [23] employed DANP to evaluate intelligent wearable Internet-of-Things devices and determined the priority level of each dimension and criterion on the basis of which manufacturers can research and develop strategies to improve the quality of such devices. The tourism industry has struggled since the outbreak of the COVID-19 pandemic; to combat these challenges, the Taiwanese government has launched a training program for travel agencies.…”
Section: Danpmentioning
confidence: 99%